Management of mental health disorders in HIV-positive patients - Southern African HIV Clinicians Society (AOSIS, 2013)
These guidelines are intended as a reference document to assist HIV nurse and doctor clinicians in managing mental health disorders. It is intended to improve awareness, knowledge and capacity to support patients living with HIV and mental health disorders.